Race, taste, class and cars - Alam, Yunis ca. 20./21. Jh (Policy Press, 2020)
Love them or hate them, most of us have an opinion about cars. If not the cars themselves, then it's driver competence and behaviour that can offend us. And then there's modification: alloy wheels, custom audio systems and bespoke paint jobs. For some, changing the look, feel and sound of a car says something about themselves, but for others, such enhancements signify a lack of taste, or even criminality. In subtle and complex ways, cars transmit and modify our identities behind the wheel. As a symbol of independence and freedom, the car projects status, class, taste and, significantly, embeds racialisation. Using fascinating research from drivers, including first-person accounts as well as exploring hip-hop music and car-related TV shows, Alam unpicks the ways in which identity is rehearsed, enhanced, interpreted